Building a BeagleBone Black Super Cluster : build and configure your own parallel computing Beowulf cluster using BeagleBone Black ARM systems /: build and configure your own parallel computing Beowulf cluster using BeagleBone Black ARM systems. (2014) - Reichel, Andreas Josef
No abstract available